Acute Kidney Injury in Cases of COVID-19 Without Existing Kidney Disease: Does It Differ at Various Stages of the Disease? - Murt, Ahmet; Dinçer, Mevlüt Tamer; Karaca, Cebrail; Trabulus, Sinan; Karaali, Rıdvan; Balkan, İlker İnanç and Seyahi, Nurhan and Altıparmak, Mehmet Rıza (Cerrahpaşa Medical Journal, 2022)
Objective: Kidney involvement in coronavirus disease 19 may manifest as acute kidney injury. This study aimed to analyze and compare acute kidney injuries in different stages of coronavirus disease 19 on patients without previous kidney diseases. Methods: A total of 1056 hospitalized coronavirus disease 19 patients were retrospectively evaluated, and 89 patients who developed acute kidney injury but did not have prior kidney diseases were involved in the final analysis. Acute kidney injury was defined according to Kidney Diseases: Improving Global Outcomes criteria. Patients were classified into 3 groups, those who had acute kidney injury on admission, those who developed acute kidney injury in the first week, and those who developed acute kidney injury starting from the seventh day. Electrolytes, acid–base status, and changes in the inflammatory markers were compared. Results: Twenty-nine patients (33%) had acute kidney injury on admission, 33 (37%) patients developed acute kidney injury in the first week, and 27 (30%) developed acute kidney injury after the first week. Acute kidney injuries that were seen on hospital admission day were generally transient. Patients who developed acute kidney injury after the seventh day had higher peak C-reactive protein (CRP) and D-dimer levels and lower nadir lymphocyte counts (P = .000, .004, and .003, respectively). Patients who developed acute kidney injury after the first week had significantly more intensive care unit admission and higher mortality, reaching as high as 62% and 44%, respectively (P = .001 and .009). Cox regression analysis revealed that increasing creatinine (P = .02; OR = 2.83; 95% CI: 1.45-5.53) and ferritin levels (P = 0.04; OR = 1.62; 95% CI: 1.16-2.05) were related to the mortality. Conclusion: Acute kidney injury in different stages of coronavirus disease 19 may have different characteristics and outcomes. Acute kidney injury that develops later tends to present with higher creatinine levels and has a worse prognosis. Cite this article as: Murt A, Dinçer MT, Karaca C, et al. Acute kidney injury in cases of COVID-19 without existing kidney disease: does it differ at various stages of the disease? Cerrahpaşa Med J. 2022;46(1):35-43.